Cross Sectional Study to Assess Knowledge about Health Effect of Tobacco Use & Tobacco User's Quitting Attitude among Rural Senior Citizens - Tarique Ibrahim; Rashmi Bhujade; Arun Kumar Wanjpe; Dharampal singh Chouhan (Medsci Publications, 2020)
Background Phenomenon of "population graying" became a matter of apprehension for stake holders today. Exposure to various insecurities has made Senior citizens's life more difficult. Health issues & co-morbidities are major concern in this age. Tobacco use is one of the major risk factor for many diseases. Methodology-Cross sectional community based study was conducted on 500 senior citizens of a block of rural field practice area of a teaching hospital with the objectives of to assess the awareness about health effects of tobacco & quitting attitude among tobacco users. Data was collected with the help of proforma & analyzed with the help of spss -20.Chi square test was applied for showing significant association. Results- Prevalence of awareness regarding health effect of tobacco use was found to be 56.6%.Knowledge of health effects of smoking was significantly associated with age, sex, religion, marital status, literacy & occupation. Prevalence of positive quitting attitude was found to be 35.4%.Positive quitting attitude was significantly associated with gender, literacy, occupation, knowledge regarding health effect of tobacco use & type of tobacco use. Conclusion -Knowledge about health effect of tobacco use was found to be significantly associated with positive quitting attitude. In order to make aging healthy, deliberate sensitization & effective public action plans are needed that can alter the adverse consequences of graying.